Communication Technology Practices Used by Midwives with Pregnant Women/people in Aotearoa New Zealand to Ensure Quality Maternal and Newborn Care - Wakelin, Karen J; McAra-Couper, Judith; Fleming, Tania; Erlam, Gwen D. (Springer Publishing Company, 2024)
INTRODUCTION: Communication was identified as a component of high-quality maternity care within an evidence-informed Quality Maternal and Newborn Care framework. Communication technology has been shown to enhance relationships midwives develop with their clients; however, concerns with the safety of the communication have been identified. AIM: This article reports on the contribution that communication technology makes toward quality care when used within a continuity of care relationship between midwives and their pregnant clients. METHODS: This article reports on phase 2A of a multiphase study. Semistructured interviews were conducted with lead maternity carer midwives using the online platform Microsoft Teams. Midwives who had previously undertaken an online survey in phase 1A and had indicated interest in participating in an online interview were emailed an invitation to participate. Fourteen midwives responded to the email invitation. Thematic analysis was used to analyze the interview data. FINDINGS: The findings indicate that communication technology facilitates quality care within a midwifery model of continuity of care. This is achieved in two ways through (a) connectedness and being known and (b) an awareness of challenges which in turn enables midwives to develop strategies for ensuring quality care. DISCUSSION: Communication technology, when used within a continuity of care relationship, facilitates quality care. It does this through enabling a connection continuation of connectedness and knowingness which enables midwives to negotiate safe and appropriate means for contact. It also privileges midwives with knowledge of challenges when using communication technology and enables strategies to be developed.
Keywords: 32 Biomedical and Clinical Sciences; 4204 Midwifery; 4205 Nursing; 42 Health Sciences; 3215 Reproductive Medicine; Reproductive health and childbirth; 3 Good Health and Well Being; 1110 Nursing; 1114 Paediatrics and Reproductive Medicine; 1199 Other Medical and Health Sciences; 3215 Reproductive medicine; 4204 Midwifery